Aggregate density forecast of models using disaggregate data - A copula approach - Kenneth Sæterhagen Paulsen; Tuva Marie Fastbø; Tobias Ingebrigtsen (Norges Bank, 2022)
We propose a novel copula approach to producing density forecasts of economic aggregates combining models using disaggregate data. Our copula approach is more flexible compared to existing techniques, because it is applicable to any econometric model that produces density forecasts. We construct a set of Monte Carlo studies to investigate the properties of the suggested approach. In our empirical application, we use the Norwegian index for goods consumption (VKI) and the Norwegian consumer price index for underlying inflation (CPI-ATE). We find that the copula approach compares well to alternative methods using recursive out-of-sample estimation.
hdl:11250/2997500
Keywords: C53; E27; 330; Aggregate forecast; disaggregates; density forecast; copula